Improvement of phase structure and energy storage properties of [(0.72-x)Bi0.5Na0.5TiO3-0.28SrTiO3-xBaZr0.05Ti0.95O3] lead-free ceramics. Issue 1 (10th December 2022) - Panpho, Phakakorn; Thongmee, Navavan; Mathrmool, Krailas; Unruan, Muangjai; Vitayakorn, Narathip; Sumang, Rattiphorn
Abstract: Lead-free [(0.72- x )Bi0.5 Na0.5 TiO3 -0.28SrTiO3 - x BaZr0.05 Ti0.95 O3 ] ceramics (abbreviated as BNT-ST- x BZT), x  = 0, 0.03, 0.05, 0.07, 0.10, and 0.15 wt.%, were prepared by conventional solid-state reaction method. The effect of x (BZT) content on phase structure, microstructure, dielectric, ferroelectric, and energy storage properties of BNT-BT- x (BST) ceramics was studied. The samples of the study were analyzed through X-ray diffraction (XRD). The XRD patterns were analyzed using Rietveld refinement. The XRD revealed a single-phase perovskite for all the samples with coexisting rhombohedral and tetragonal phases. It shows the increasing of x (BZT) content and, more tetragonal distortion of the phase. The scanning electron micrographs (SEM) of all the samples displayed spherical-like morphology. The grain growth inhibited by increasing of x (BZT) content. The average of grain size decreased from 2.74 µm to 0.65 µm with BZT content. The highest density ( ρ  = 5.31 ± 0.11 g/cm 3 ), recoverable energy storage density ( W rec = 0.234 J/cm 3 ), and energy storage efficiency ( η  = 90%) at 30 kV/cm were found in the composition of x (BZT) = 0.05 wt.%.